Dark and gritty/slick and glossy: Genre, Nollywood and Lagos. (1st December 2019) - Ryan, Connor
AbstractIn this article, I am concerned principally with Taxi Driver (Oriahi, 2015), Gbomo Gbomo Express (Taylaur, 2015), Just Not Married (Patrick, 2016), Ojukokoro (Greed) (Olaitan, 2016) as well as Catch.er (Taylaur, 2017). These films are characterized as much by the depiction of clever criminals as the cultivation of a cynical disposition from which transgressions of this sort appear stylish and violence is rendered 'cool'. Almost all of them turn on a scheme to dupe others of a large sum of money, and are punctuated by backstabbing partners in crime, tables turning by chance, edgy armed standoffs and a surprising number of bodies in car trunks. Given the dark portrait of Lagos these films present, one might be inclined to read the genre cycle as a reiteration of the role Lagos has historically played as embodiment of popular anxieties concerning insecurity, material inequality and social breakdown. And yet, in recent years, conditions within the city have markedly improved over those of the deepest point of urban crisis in the 1990s when Lagos was, indeed, paralysed by a generalized condition of insecurity and dysfunction. New Nollywood's repertoire of film styles has expanded to include international film cycles and genres such as romantic comedies, psychological thrillers, police procedurals, among others. This raises important questions about the nature of correspondences between cinema and the city, such as whether New Nollywood genre films tell us anything about social, cultural or historical circumstances in Lagos, or the place the city occupies in the popular imagination, for instance. Recent upmarket film noirs speak, instead, to the evolution of Lagos as a media capital. I examine the different kinds of work genre performs in New and Old Nollywood films and propose a number of ways to critically interpret genre's various registers.